DAMPAK PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 PADA PEMAHAMAN SISWA TERHADAP MATA PELAJARAN PENDIDIKAN STUDI KASUS DI SDN 2 YOSOMULYO KECAMATAN GAMBIRAN KABUPATEN BANYUWANGI - Aan Ari Stepanes; Widia Darma; Sukarti (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
Online learning of Buddhist education at SDN 2 Yosomulyo Had Various obstacles and problems arose that had an impact on students’ understanding. That was the reason for researchers to conduct resech subjects. This study aimed to (1) find out online learning process on Buddhism and (2) to analyzy the impact of online learning on Students’ understanding of Buddhism subject at SDN 2Yosomulyo Gambiran subdistrict, Banyuwangi.This studi used a qualitative method. The research approach was a case study. The location of the research wass at SDN 2 Yosomulyo. When the research was conduted from February to July 2021, the data qualitative research were collected thrugh observation, interviews and documentation, the valididy of the data used Triangulation, data analysis techniques refferring to the Miles & Huberman concept.The result of this study indicated that (1) the online learning process of Buddhist Education at SDN 2 Yosomulyo, was carried out via Whatsapp, Zoom, Google meet and various obstacles in the from of: limited facilites, lack of mastery of technology by students, material was not understood, lack parental assistance when learning online, lack of adaptation to online learning, (2) The Impact of online learning on students’ understanding of buddhist education subjects, namely students have difficulty in retell, give opinions and provide conclusions on buddhist education subjects by teachers when oline learning